The inspirational untold stories of secondary mathematics teachers - Artzt, Alice F.; Curcio, Frances R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Personal story telling is a powerful and interesting medium through which one can share experiences, insights, successes, and difficulties in meaningful contexts. Teaching in general, and mathematics teaching in particular, is much more than what meets the eye. Most people have only experienced teaching from the vantage point of a student and have impressions of teachers and teaching that are simplistic and usually totally incorrect. The lives of mathematics teachers are varied and contrary to what one might think they are. The journeys of exemplary in-service teachers are not linear; there are many bends, potholes, and detours through which they have navigated. The "road conditions" of teaching are fodder for the 12 untold stories collected in this volume, whose authors graduated from a special four-year undergraduate mathematics teacher preparation program, containing innovative components, many of which are revealed through the experiences described in their stories. The range of narratives vary in every possible way, from the reasons they became mathematics teachers, to the number of years teaching, to the experiences encountered while teaching, to the different roles they have assumed throughout their careers. Nevertheless, one strand permeates all of the stories--their passion for what they do and their ability to reflect on early college experiences that contribute to their performance. These inspiring narratives will shed light on the developmental processes of mathematics teachers, what it means to teach mathematics, and the components of a secondary mathematics teacher preparation program that can contribute to their expertise"--